Influence of Cereal Rye Management on Weed Control in Soybean - Vollmer, Kurt M.; VanGessel, Mark J.; Johnson, Quintin R.; Scott, Barbara A. (Frontiers in Agronomy, 2020)
A common stated goal for using cereal rye as a cover crop is improving soil health and as part of integrated weed management programs. Despite this, cereal rye biomass is often not managed for optimal weed suppression. This study was conducted to evaluate the effects of managing cereal rye as part of an integrated weed management strategy in soybean. Treatments consisted of cereal rye managed for high, moderate, or no biomass; cereal rye terminated 20 d or 10 d before soybean planting; and a residual herbicide treatment applied at cereal rye termination. Cereal rye provided better control of winter annual weeds at soybean planting compared to no cereal rye. Winter annual weed control was better if cereal rye was terminated at 20 d before soybean plant than 10 d. Including a residual herbicide provided better control of Palmer amaranth, Large crabgrass, and morningglory spp. when rated 4 wks after planting. Summer annual weed control with high and moderate levels of cereal rye varied by weed species. Palmer amaranth control responded to the three levels of cereal rye biomass in the absence of residual herbicides; yet only the high level of rye improved morningglory spp. control. Large crabgrass control was similar for moderate and high levels of cereal rye biomass. Furthermore, cereal rye terminated closer to planting provided better control of summer annual weeds than early-terminated cereal rye. Our results demonstrate the importance of cover crop management when incorporating cereal rye into an integrated weed management program for soybean.